Penerapan Metode Jama’ Bin Nazhar Pada Program Tahfizhul Qur’an Di SMP IT Luqmanul Hakim - Jannah, Suci Nurul; Setiawan, Hasrian Rudi (Al-Ulum: Jurnal Pendidikan Islam, 2024)
The subject of this research is the design, implementation of the jama' bin-nazhar method as well as supporting and inhibiting factors for teaching tahfidz at SMP IT Luqmanul Hakim Sei Mencirim class VII for the 2023/2024 academic year. This research requires a combination of quantitative and qualitative methods with data collection techniques: monitoring, interviews and data analysis and archiving. The style of explaining the instructions goes to the level of deriving the instructions, stating statistics and inference. The first research product is the planned implementation of the identified jama' bin-nazhar method while carrying out reading activities simultaneously under the guidance of a master and memorizing, paying attention to the makhrijul letters, tajwid and tahsin information for each student. Second, the introduction of the jama' bin-nazhar method in learning tahfidz through preparation activities for reading learning prayers. then the core activity continued with the application of the jama' bin nazhar method in memorizing the Al-Qur'an which was carried out as a group, namely. These memorized verses are read as a group or together under the guidance of a teacher who teaches tahfiz subjects. Each student then completes additional memorization and muroja'ah through verbalizing and reviewing the Al-Quran manuscripts independently, passed on by entrustment to the teacher. At the end of the action is carried out through assessment and encouragement. In the future, the third product, supporting aspects and obstacles to the implementation of the Jama' bin Nazhar method are: 1) learning planning. 2) the thrill of learning. 3) student responsiveness. 4) the state of mind of students. In fact, the barrier aspects are: 1) boredom and students' inability to determine their own destiny. 2) quick understanding, which some students lack.